Efficacy of non-obstructive aortic angioscopy for detecting a thoracic aortic graft rupture: a case report - Fumio Yamana; Koichi Maeda; Yuma Hamanaka; Noriko Kodani; Keitaro Domae; Masatoshi Hata; Yoshiharu Higuchi; Yukitoshi Shirakawa; Takafumi Masai (Surgical Case Reports)
Abstract Background Non-anastomotic thoracic aortic graft rupture is extremely rare and difficult to diagnose. Non-obstructive general angioscopy can help monitor the aortic intima and detect the locations of abnormal findings, while aortic angioscopy can detect vulnerable plaques in the aorta, which are difficult to visualize using conventional diagnostic methods. Herein, we report the case of a patient with non-anastomotic thoracic aortic graft rupture diagnosed using non-obstructive aortic angioscopy. Case presentation An 85-year-old man who had undergone total arch replacement 5 years prior complained of chest pain. Emergent contrast-enhanced computed tomography (CT) revealed an intra-mediastinal hematoma around the vascular graft of the ascending aorta and angiography revealed pooling of contrast medium on the dorsal side of the vascular graft. We suspected extravasation of the thoracic vascular graft. Aortic angioscopic examination revealed a red vascular graft defect that matched extravasation at the contralateral level of the prosthetic left common carotid artery branch. Subsequently, non-anastomotic thoracic aortic graft rupture was diagnosed. The patient underwent a two-debranching thoracic endovascular aortic repair (Zone 0) with a right subclavian artery-left common carotid artery-left subclavian artery bypass. Postoperative angiography revealed disappearance of the extravasation from the graft rupture site, patent grafted vessels with flow, and no endoleak. Follow-up CT at 6 months postoperatively showed no extravasation. Conclusions To our knowledge, this is the first report of non-anastomotic thoracic aortic graft rupture detected using non-obstructive aortic angioscopy. Aortic angioscopy can help establish a definitive diagnosis in patients with aortic graft rupture.